2021
DOI: 10.1098/rsos.210565
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular hydrogen bond ruptured by graphite with different lamellar number

Abstract: Intermolecular hydrogen bonds are formed through the electrostatic attraction between the hydrogen nucleus on a strong polar bond and high electronegative atom with an unshared pair of electrons and a partial negative charge. It affects the physical and chemical properties of substances. Based on this, we presented a physical method to modulate intermolecular hydrogen bonds for not changing the physical–chemical properties of materials. The graphite and graphene are added into the glycerol, respectively, by be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[37][38][39] Different from the macroscopic composite mode of solid film-liquid lubricant common in industry, Ma et al uniformly dispersed nanoscale single-layer graphene and multilayer graphite materials into glycerol and found that graphene and graphite retained the characteristics of solid lubricants in this system. [40] This phenomenon inspired us to modify the surface of graphene-like nano-MoS 2 material with a uniform liquid lubricating coating and inject it into the joint cavity. Macroscopically, the solid-solid friction between the articular surfaces is transformed into solid-liquid friction between the articular surfaces and the liquid lubricant, while microscopically, the interlayer solid-solid friction of MoS 2 is transformed into liquid-liquid friction between the hydration layers on the surface of the MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Different from the macroscopic composite mode of solid film-liquid lubricant common in industry, Ma et al uniformly dispersed nanoscale single-layer graphene and multilayer graphite materials into glycerol and found that graphene and graphite retained the characteristics of solid lubricants in this system. [40] This phenomenon inspired us to modify the surface of graphene-like nano-MoS 2 material with a uniform liquid lubricating coating and inject it into the joint cavity. Macroscopically, the solid-solid friction between the articular surfaces is transformed into solid-liquid friction between the articular surfaces and the liquid lubricant, while microscopically, the interlayer solid-solid friction of MoS 2 is transformed into liquid-liquid friction between the hydration layers on the surface of the MoS 2 .…”
Section: Introductionmentioning
confidence: 99%